The phenomenon of social loafing in high school students - Gustiani, Hesti; Yeni, Frischa Meivilona; Neviyarni, Neviyarni; Febriani, Rahmi Dwi; Zahri, Triave Nuzila (Universitas Negeri Padang, 2025)
Adolescents tend to join social groups based on similarities and comfort. In group learning, all members are expected to participate equally; however, this is not always the case. Individuals often exert less effort in groups compared to working independently, a phenomenon known as social loafing. This study aimed to describe students' social loafing based on two dimensions: dillution effect and immediacy gap. Using a quantitative descriptive method, the study involved 216 high school students selected through proportional random sampling from a population of 440 students. Data were collected using a validated social loafing scale. Results indicated that social loafing based on the dillution effect dimension was categorized as low (48.15%), while social loafing based on the immediacy gap dimension was categorized as medium (54.63%). School counselor are encouraged to mitigate social loafing through information services, individual counseling, and group counseling interventions.